Glassy carbon electrode based on Cu-MOF-coated MnCO3 modification, preparation method of glassy carbon electrode and electrochemical sensor

By modifying Cu-MOF@MnCO3 on the glass carbon electrode of the electrochemical sensor and combining the dual signal mechanism of mercury ions and Cu2+, the problem that electrochemical sensors are prone to false positives when detecting mercury ions is solved, improving the accuracy of detection and anti-interference.

CN119715727AActive Publication Date: 2025-03-28JIANGSU UNIV +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411903142.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

Electrochemical sensors are prone to false positives when detecting mercury ion content, mainly because they are sensitive to certain interfering substances, resulting in incorrect detection results.

Method used

By modifying Cu-MOF@MnCO3 on the glass carbon electrode, Cu-MOF is used to provide the internal reference signal. The signal generated when Cu2+ is reduced to Cu+ is combined with the signal of the mercury ion itself, effectively avoiding false positive phenomena.

Benefits of technology

The anti-interference, stability and reliability of electrochemical sensors for mercury ion detection is improved, misjudgment is reduced, detection accuracy is improved, and ultra-sensitive electrochemical detection of mercury ions is realized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119715727A_ABST
    Figure CN119715727A_ABST
Patent Text Reader

Abstract

The invention provides a glassy carbon electrode based on Cu-MOF-coated MnCO3 modification, a preparation method of the glassy carbon electrode and an electrochemical sensor. The preparation method comprises the following steps: S1, preparing Cu-MOF-coated MnCO3 powder; s2, polishing, cleaning and drying the surface of the glassy carbon electrode for later use; and S3, dissolving Cu-MOF-coated MnCO3 powder in DMF, dropwise coating the Cu-MOF-coated MnCO3 powder on the surface of the glassy carbon electrode treated in the step S2, and heating and drying the Cu-MOF-coated MnCO3 powder under an infrared lamp to obtain the Cu-MOF-coated MnCO3 modified glassy carbon electrode. On one hand, by combining a signal generated by the mercury ions and an internal reference signal generated when Cu < 2 + > and Cu < + > in Cu-MOF are subjected to a reduction reaction, the false positive phenomenon is effectively avoided, and the anti-interference performance, stability and reliability of the electrochemical sensor on mercury ion detection are improved. On the other hand, double signals are amplified through MnCO3, the detection range of the electrochemical sensor can be further widened, the detection limit can be reduced, and the electrochemical sensor is particularly suitable for detection of trace mercury ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of mercury ion detection, and in particular to a glassy carbon electrode modified based on Cu-MOF@MnCO3, a preparation method thereof, and an electrochemical sensor. Background Art

[0002] Mercury ion is a highly toxic heavy metal ion that poses a serious threat to the environment and human health. Due to its widespread presence in industrial wastewater, pesticide residues and the natural environment, mercury pollution has received widespread attention worldwide. Therefore, it is particularly important to develop rapid, sensitive and specific mercury ion detection technology. Traditional mercury ion detection methods include atomic absorption spectroscopy (AAS), inductively coupled plasma mass spectrometry (ICP-MS), etc. Although these methods have high sensitivity and accuracy, they usually require complex sample pretreatment processes, expensive instruments and equipment, and professional operators, making it difficult to achieve rapid on-site detection.

[0003] With the development of science and technology, electrochemical detection technology has gradually become a research hotspot in the field of mercury ion detection due to its advantages such as low cost, portability, easy operation and real-time monitoring capabilities. Electrochemical sensors quantitatively analyze the presence of target substances, such as mercury ions, by measuring changes in electrical signals. This type of sensor usually consists of a working electrode, a reference electrode and an auxiliary electrode. When mercury ions react with the surface of the working electrode, changes in current, voltage or resistance are triggered and thus detected. However, although electrochemical sensors perform well in mercury ion detection, they are not perfect. One of the important defects is that false positives are prone to occur. This is mainly because electrochemical sensors are also sensitive to certain interfering substances, which may produce similar signals on the electrodes, leading to erroneous detection results. Summary of the invention

[0004] Aiming at the problem that electrochemical sensors are prone to false positives when detecting mercury ion content, the present invention provides a glassy carbon electrode modified with Cu-MOF@MnCO3 and a preparation method thereof, as well as an electrochemical sensor, which combines the signal generated by mercury ions themselves and the Cu in Cu-MOF. 2+ Reduction to Cu + The internal reference signal generated during the measurement can effectively avoid the false positive phenomenon, thereby improving the anti-interference, stability and reliability of the electrochemical sensor for mercury ion detection.

[0005] The present invention achieves the above technical objectives through the following technical means.

[0006] A method for preparing a glassy carbon electrode modified with Cu-MOF@MnCO3 comprises the following steps:

[0007] S1. Preparation of Cu-MOF@MnCO3 powder

[0008] S1.1: Add 2-aminoterephthalic acid and CuNO3·3H2O to DMF at room temperature, transfer to a polytetrafluoroethylene reactor after ultrasonic treatment, and stand at 90-100°C for 24-26 hours; then cool to room temperature, centrifuge, wash and dry the obtained precipitate to obtain Cu-MOF powder;

[0009] Wherein, the molar ratio of 2-aminoterephthalic acid to CuNO3·3H2O is 2 to 4:5;

[0010] S1.2: Add the Cu-MOF powder in step S1.1 and an equal amount of MnCO3 powder to DMF, perform ultrasonic treatment and centrifugal separation, wash the obtained precipitate, and vacuum dry it to obtain Cu-MOF@MnCO3 powder;

[0011] S2. Electrode Pretreatment

[0012] Take a glassy carbon electrode, grind and polish the surface of the glassy carbon electrode, then clean the surface of the glassy carbon electrode, heat and dry it under an infrared lamp for standby use;

[0013] S3. Electrode Modification

[0014] Cu-MOF@MnCO3 powder is added to DMF, and a suspension is obtained after ultrasonic treatment; the suspension is dropwise applied onto the surface of the glassy carbon electrode treated in step S2, and heated and dried under an infrared lamp to obtain a Cu-MOF@MnCO3 modified glassy carbon electrode.

[0015] Furthermore, in step S1.1, the duration of the ultrasonic treatment is 3 to 7 minutes; the working parameters of the centrifugal separation are: the rotation speed is 8000 to 9000 rpm, and the centrifugal time is 3 to 6 minutes; the selected detergent is anhydrous ethanol; the drying temperature is 50 to 70°C, and the drying time is 18 to 20 hours.

[0016] Furthermore, in step S1.2, the method for preparing the MnCO3 powder comprises the following steps:

[0017] S1.2.1: Mix ethylene glycol and ultrapure water in a ratio of 1:1, add MnSO4 powder, and stir under ultrasonication until completely dissolved to obtain a mixed solution;

[0018] S1.2.2: At room temperature, add NaHCO3 solution dropwise to the mixed solution in step S1.2.1 and continue stirring for 4 to 6 hours; then centrifuge and wash the obtained precipitate, and vacuum dry it to obtain MnCO3 powder.

[0019] Furthermore, in step S1.2.2, the molar ratio of MnSO4 to NaHCO3 is 1:1 to 1.5.

[0020] Furthermore, in step S1.2, the duration of the ultrasonic treatment is 35 to 50 minutes; the working parameters of the centrifugal separation are: the rotation speed is 8000 to 9000 rpm, and the centrifugal time is 4 to 6 minutes; the selected detergent is anhydrous ethanol; the vacuum drying temperature is 50 to 70°C, and the drying time is 10 to 14 hours.

[0021] Furthermore, in step S2, the surface of the glassy carbon electrode is ground and polished in turn using aluminum oxide powders with particle sizes of 0.3 μm and 0.05 μm; and the ground and polished glassy carbon electrode is cleaned using anhydrous ethanol and ultrapure water, respectively.

[0022] Furthermore, in step S3, the relationship between the drop coating amount of Cu-MOF@MnCO3 and the diameter of the glassy carbon electrode is 0.5×10 -3 ~1×10 -3 mg:1mm.

[0023] Furthermore, in step S3, the ultrasonic treatment duration is 20 to 40 minutes.

[0024] A glassy carbon electrode modified with Cu-MOF@MnCO3 prepared by any of the above preparation methods.

[0025] An electrochemical sensor comprising the glassy carbon electrode.

[0026] The present invention uses Cu-MOF to provide an internal reference signal. The abundant metal ions inside Cu-MOF give it good electrochemical properties. In the electrochemical detection process, in addition to the signals that may be generated by mercury ions themselves, the Cu of Cu-MOF itself 2+ A reduction reaction will occur to generate an internal reference signal. This double signal phenomenon effectively avoids the occurrence of false positives. The ion reactions that occur in this process are as follows:

[0027] Hg 2+ +2e - →Hg (detection signal)

[0028] Cu 2+ +e - →Cu + (Internal reference signal)

[0029] The beneficial effects of the present invention are as follows:

[0030] 1. The present invention is based on Hg 2+ Reduction produces a detection signal, and Cu 2+The dual-signal mechanism that generates the internal reference signal is restored to effectively avoid false positives, prevent misjudgment, and improve detection accuracy.

[0031] 2. Cu in the present invention 2+ Reduced to Cu + , some Cu + Released into the electrolyte, the holes on the surface of the sensing electrode increase, promoting the Hg 2+ The reduction reaction makes the detected Hg 2+ The signal peak value of Hg 2+ The effect of detecting signal amplification. At the same time, when Hg 2+ As the content increases, more Hg 2+ Will lead to more Cu 2+ Reduced to Cu + , and more Cu + This will further promote Hg 2+ reduction, making it easier to detect, forming a positive feedback loop.

[0032] 3. The MnCO3 in the present invention has a porous structure and good electrocatalytic properties to Hg 2+ The detection has obvious signal amplification effect, which can further broaden the detection range of electrochemical sensors and reduce the detection limit. It is particularly suitable for the detection of trace mercury ions.

[0033] 4. The MnCO3 in the present invention has good biocompatibility and cyclic stability, is easily combined with Cu-MOF, and the two particles of Cu-MOF and MnCO3 are adsorbed and aggregated together. The two porous particles are composited, which increases edge defects and provides more active sites for mercury ion attachment, which is more conducive to the redox reaction.

[0034] 5. The electrochemical sensor obtained by surface-modifying the glassy carbon electrode using Cu-MOF@MnCO3 as a modifier and DMF as a film-forming agent is used for ultrasensitive electrochemical detection of mercury ions, showing a wide detection range and a low detection limit for mercury ions. In addition, the dual-signal electrochemical sensor has good anti-interference, reliability, repeatability and applicability, and can sensitively, accurately and efficiently analyze and detect mercury ions in water. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the microscopic morphology of the Cu-MOF@MnCO3 powder described in Example 1.

[0036] Figure 2 2. XRD patterns of Cu-MOF@MnCO3 powder, Cu-MOF powder and MnCO3 powder in Example 1.

[0037] Figure 3 FTIR spectra of Cu-MOF@MnCO3 powder, Cu-MOF powder and MnCO3 powder in Example 1.

[0038] Figure 4 This is a flow chart for the preparation and performance testing of the glassy carbon electrode modified with Cu-MOF@MnCO3 as described in Example 1.

[0039] Figure 5 For different Hg in Example 1 2+ Linear relationship curve between DPV current signal of mercury ion and copper ion and mercury ion concentration under different concentrations.

[0040] Figure 6 a is the bare glassy carbon electrode in comparative example 3 in the presence of 10 μM Hg 2+ HAc-NaAc buffer (pH = 4.5), and Hg-free 2+ Comparison of DPV current signals in HAc-NaAc buffer (pH=4.5).

[0041] Figure 6 b is the MnCO3 modified glassy carbon electrode in comparative example 2 in the presence of 10 μM Hg 2+ HAc-NaAc buffer (pH = 4.5), and Hg-free 2+ Comparison of DPV current signals in HAc-NaAc buffer (pH=4.5).

[0042] Figure 6 c is the Cu-MOF modified glassy carbon electrode in comparative example 1 in the presence of 10 μM Hg 2+ HAc-NaAc buffer (pH = 4.5), and Hg-free 2+ Comparison of DPV current signals in HAc-NaAc buffer (pH=4.5).

[0043] Figure 6 d is the Cu-MOF@MnCO3 modified glassy carbon electrode in Example 1 in the presence of 10 μM Hg 2+ HAc-NaAc buffer (pH = 4.5), and Hg-free 2+ Comparison of DPV current signals in HAc-NaAc buffer (pH=4.5). DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.

[0045] Example 1

[0046] The preparation method of the glassy carbon electrode modified by Cu-MOF@MnCO3 in this embodiment includes the following steps:

[0047] S1. Preparation of Cu-MOF@MnCO3 powder

[0048] S1.1: At room temperature, 0.12 g of 2-aminoterephthalic acid and 0.25 g of CuNO3·3H2O were added to 10 mL of DMF, and after ultrasonic treatment for 3 to 7 min, the mixture was transferred to a polytetrafluoroethylene reactor and allowed to stand at 100 °C for 25 h. The mixture was then cooled to room temperature, centrifuged at 8000 rpm for 5 min, and the precipitate was washed three times with anhydrous ethanol and dried at 60 °C to obtain Cu-MOF powder.

[0049] S1.2: Add 50 mg of the Cu-MOF powder in step S1.1 and an equal amount of 50 mg of MnCO3 powder to DMF, ultrasonically treat for 40 min, and then centrifuge at 9000 rpm for 5 min. Wash the obtained precipitate with anhydrous ethanol and vacuum dry it at 60°C for 12 h to obtain Cu-MOF@MnCO3 powder.

[0050] Microscopic morphology analysis:

[0051] The morphology of the Cu-MOF@MnCO3 powder prepared in this example was characterized and analyzed using a field emission scanning electron microscope (MIRA, TESCAN). Figure 1 This is the microscopic morphology of Cu-MOF@MnCO3 described in this embodiment. As shown in the figure, the two particles of Cu-MOF and MnCO3 are adsorbed and aggregated together, and the two porous particles are composited, which increases the edge defects and provides more active sites for the attachment of mercury ions, which is more conducive to the redox reaction.

[0052] XRD analysis:

[0053] XRD was used to analyze the crystal phase of Cu-MOF@MnCO3 powder, Cu-MOF powder and MnCO3 powder. Figure 2 3 is the XRD spectrum of the Cu-MOF@MnCO3 powder, Cu-MOF powder and MnCO3 powder in this embodiment. The results show that in the XRD spectrum of Cu-MOF@MnCO3 powder, characteristic diffraction peaks of Cu-MOF appear at 2θ=28.8°, 14.96°, 16.9° and 24.78°, and characteristic diffraction peaks of MnCO3 appear at 2θ=24.25°, 31.36°, 37.52°, 41.42°, 45.19° and 51.6°, proving that the crystal structures of both Cu-MOF and MnCO3 are retained in the Cu-MOF@MnCO3 powder.

[0054] FTIR analysis:

[0055] The crystal phase of Cu-MOF@MnCO3 powder was analyzed by FTIR. Figure 3 The FTIR spectra of Cu-MOF@MnCO3 powder, Cu-MOF powder and MnCO3 powder in this example show that the FTIR spectrum of Cu-MOF@MnCO3 is at 3254cm -1 、1574cm -1 、1369cm -1 、764cm -1 The stretching vibration peak of Cu-MOF appeared at 1402 cm -1 、3408cm -1 The stretching vibration peak of MnCO3 appeared at the position, which further proved the successful preparation of the Cu-MOF@MnCO3 powder in terms of crystal structure.

[0056] XPS analysis:

[0057] XPS was used to analyze the elemental valence of Cu-MOF@MnCO3 powder. The results showed that the peaks of C, O, N, Cu and Mn, which are essential for the composition of Cu-MOF@MnCO3 composite materials, appeared in the full spectrum. The deconvolution peaks of the chemical bonds corresponding to Cu-MOF and MnCO3 appeared in the fine spectrum of the five elements C, O, N, Cu and Mn, and the peaks of Cu 2+ and Cu + Two valence states demonstrate the successful preparation of the Cu-MOF@MnCO3 powder in terms of elemental composition.

[0058] S2. Electrode Pretreatment

[0059] A glassy carbon electrode with a diameter of 6 mm was taken, and the surface of the glassy carbon electrode was polished and polished with alumina powders with particle sizes of 0.3 μm and 0.05 μm in turn to obtain a mirror-like surface. The glassy carbon electrode was then rinsed with anhydrous ethanol and ultrapure water respectively, heated and dried under an infrared lamp, and set aside.

[0060] S3. Electrode Modification

[0061] 1.5 mg Cu-MOF@MnCO3 powder was added to 1.5 mL DMF and ultrasonically treated for 40 min to obtain a suspension. 4 μL of the suspension was dropwise applied onto the surface of the glassy carbon electrode treated in step S1 and heated and dried under an infrared lamp to obtain a Cu-MOF@MnCO3 modified glassy carbon electrode. Figure 4 This is a diagram of the preparation process and performance test of the Cu-MOF@MnCO3 modified glassy carbon electrode described in this embodiment.

[0062] The method for preparing the MnCO3 powder used in the above step S1.2 comprises the following steps:

[0063] S1.2.1: Mix ethylene glycol and ultrapure water in a ratio of 1:1, add 2.3 g of MnSO4 powder, and stir under ultrasonication until completely dissolved to obtain a mixed solution.

[0064] S1.2.2: At room temperature, 110 mL of 150 mM NaHCO3 solution was added dropwise to the mixed solution in step S1.2.1 and stirred for 6 h. The mixture was then centrifuged at 11000 rpm for 12 min, the precipitate was washed with ultrapure water, and MnCO3 powder was obtained after vacuum drying at 70°C for 13 h.

[0065] The Cu-MOF@MnCO3 modified glassy carbon electrode prepared in Example 1 was used as the working electrode, the saturated calomel electrode was used as the reference electrode, the platinum electrode was used as the counter electrode, and HAc-NaAc solution (pH = 4.5) was used as the buffer solution to measure the concentrations of Hg at different concentrations (0.10, 0.15, 0.30, 0.60, 0.90, 1.20, 1.50, 2.00, 2.50 μM). 2+ The detection was performed to obtain the DPV current signal curves of mercury ions and copper ions, and the mercury ion concentrations and the corresponding mercury ion and copper ion peak current values ​​were recorded in Table 1. Figure 5 This is the linear relationship curve between the DPV current signal of mercury ions and copper ions and the mercury ion concentration.

[0066] Table 1. Peak current value records of mercury ions and copper ions at different ion concentrations

[0067]

[0068] It can be seen from Table 1 that as Hg 2+ As the concentration of Cu 2+ The peak value and Hg 2+ The peak value shows a linear increasing trend. Figure 5 In this embodiment, different Hg 2+ The linear relationship curve between the DPV current signal of mercury ions and copper ions at different concentrations and the mercury ion concentration is shown in the figure. The sensor detects Cu in the linear range of 0.10 to 2.50 μM. 2+ and Hg 2+ The linear response signal, linear fitting equations are respectively, mercury ion: y = 9.3152x + 0.6409, correlation coefficient R 2 =0.9994, copper ion: y=7.8386x+23.6870, correlation coefficient R 2=0.9917, and the detection limit was as low as 6.82 nM (S / N=3).

[0069] Anti-interference and stability testing:

[0070] The Cu-MOF@MnCO3 modified glassy carbon electrode prepared in Example 1 was used as the working electrode, the saturated calomel electrode was used as the reference electrode, the platinum electrode was used as the counter electrode, and the HAc-NaAc solution (pH = 4.5) was used as the buffer solution. 2+ The concentration of Co is 10 times 2+ , Cu 2+ , Fe 2+ , Mn 2+ 、Ni 2+ , Pb 2+ and Zn 2+ In the presence of 10 μM Hg 2+ The different interfering ions and the corresponding mercury ion and copper ion peak current values ​​are recorded in Table 2. The presence of interfering metal ions has an effect on the Cu 2+ and Hg 2+ The peak current of the sensor caused a slight interference, however, the maximum deviation was less than 10%. This shows that the sensor of the present invention has good anti-interference ability, because the Cu-MOF in Cu-MOF@MnCO3 is rich in -NH groups, and Hg 2+ It is a soft metal that can form a very strong chelate with -NH groups. Its binding ability with -NH groups is higher than that of other metal ions, which leads to the sensor's sensitivity to Hg 2+ The detection has good anti-interference ability.

[0071] Table 2. Peak current value records of mercury ions and copper ions under different interfering ions

[0072]

[0073] During 7 days, the Cu-MOF@MnCO3 modified glassy carbon electrode prepared in Example 1 was used as the working electrode, the saturated calomel electrode was used as the reference electrode, the platinum electrode was used as the counter electrode, and the HAc-NaAc solution (pH=4.5) was used as the buffer solution. The different days and the corresponding mercury ion and copper ion peak current values ​​were recorded in Table 3. On the 7th day, Cu 2+ The peak current of Hg 2+ The peak current decreased by 10.42%, indicating that the sensor can still maintain more than 90% of the signal after 6 days of storage. This proves that the glassy carbon electrode modified by Cu-MOF@MnCO3 has good storage stability.

[0074] Table 3. Record of peak current values ​​of mercury ions and copper ions at different storage days

[0075]

[0076] Example 2

[0077] The preparation method of the glassy carbon electrode modified by Cu-MOF@MnCO3 in this embodiment includes the following steps:

[0078] S1. Preparation of Cu-MOF@MnCO3 powder

[0079] S1.1: At room temperature, 0.10 g of 2-aminoterephthalic acid and 0.20 g of CuNO3·3H2O were added to 10 mL of DMF, and after ultrasonic treatment for 5 min, the mixture was transferred to a polytetrafluoroethylene reactor and allowed to stand at 100 °C for 24 h. The mixture was then cooled to room temperature, centrifuged at 8000 rpm for 5 min, and the precipitate was washed three times with anhydrous ethanol and dried at 60 °C to obtain Cu-MOF powder.

[0080] S1.2: Add 50 mg of the Cu-MOF powder in step S1.1 and an equal amount of 50 mg of MnCO3 powder to DMF, ultrasonically treat for 40 min, and then centrifuge at 9000 rpm for 5 min. Wash the obtained precipitate with anhydrous ethanol and vacuum dry it at 60°C for 12 h to obtain Cu-MOF@MnCO3 powder.

[0081] S2. Electrode Pretreatment

[0082] A glassy carbon electrode with a diameter of 6 mm was taken, and the surface of the glassy carbon electrode was polished and polished with alumina powders with particle sizes of 0.3 μm and 0.05 μm in turn to obtain a mirror-like surface. The glassy carbon electrode was then rinsed with anhydrous ethanol and ultrapure water respectively, heated and dried under an infrared lamp, and set aside.

[0083] S3. Electrode Modification

[0084] 1.5 mg Cu-MOF@MnCO3 powder was added to 1.5 mL DMF, and a suspension was obtained after ultrasonic treatment for 40 min. 4 μL of the suspension was dropwise applied onto the surface of the glassy carbon electrode treated in step S1, and heated and dried under an infrared lamp to obtain a Cu-MOF@MnCO3 modified glassy carbon electrode.

[0085] The method for preparing the MnCO3 powder used in the above step S1.2 comprises the following steps:

[0086] S1.2.1: Mix ethylene glycol and ultrapure water in a ratio of 1:1, add 2.0 g of MnSO4 powder, and stir under ultrasonication until completely dissolved to obtain a mixed solution.

[0087] S1.2.2: At room temperature, 100 mL of 150 mM NaHCO3 solution was added dropwise to the mixed solution in step S1.2.1 and stirred for 6 h. The mixture was then centrifuged at 10,000 rpm for 12 min, the precipitate was washed with ultrapure water, and vacuum dried at 70°C for 13 h to obtain MnCO3 powder.

[0088] Comparative Example 1

[0089] In order to verify the use effect of MnCO3 powder, this comparative example only uses the Cu-MOF powder prepared in Example 1. Specifically, the preparation method of the glassy carbon electrode modified with Cu-MOF in this comparative example includes the following steps:

[0090] S1: Take a glassy carbon electrode with a diameter of 6 mm, and use aluminum oxide powder with a particle size of 0.3 μm and 0.05 μm to grind and polish the surface of the glassy carbon electrode in turn to obtain a mirror-like surface, then rinse the glassy carbon electrode with anhydrous ethanol and ultrapure water respectively, heat and dry it under an infrared lamp, and set it aside.

[0091] S2: Add 1.5 mg of Cu-MOF powder to 1.5 mL of DMF, and ultrasonicate for 40 min to obtain a suspension. 4 μL of the suspension is dropwise applied onto the surface of the glassy carbon electrode treated in step S1, and heated and dried under an infrared lamp to obtain a Cu-MOF-modified glassy carbon electrode.

[0092] Comparative Example 2

[0093] In order to verify the use effect of Cu-MOF powder, this comparative example only uses the MnCO3 powder prepared in Example 1. Specifically, the preparation method of the glassy carbon electrode modified with MnCO3 in this comparative example includes the following steps:

[0094] S1: Take a glassy carbon electrode with a diameter of 6 mm, and use aluminum oxide powder with a particle size of 0.3 μm and 0.05 μm to grind and polish the surface of the glassy carbon electrode in turn to obtain a mirror-like surface, then rinse the glassy carbon electrode with anhydrous ethanol and ultrapure water respectively, heat and dry it under an infrared lamp, and set it aside.

[0095] S2: Add 1.5 mg of Cu-MOF powder to 1.5 mL of DMF, and ultrasonicate for 40 min to obtain a suspension. 4 μL of the suspension is dropwise applied onto the surface of the glassy carbon electrode treated in step S1, and heated and dried under an infrared lamp to obtain a MnCO3-modified glassy carbon electrode.

[0096] Comparative Example 3

[0097] In order to verify the combined use effect of Cu-MOF powder and MnCO3 powder, this comparative example does not use the above-mentioned Cu-MOF powder and MnCO3 powder. Specifically, this comparative example takes a glassy carbon electrode with a diameter of 6 mm, and uses alumina powders with particle sizes of 0.3 μm and 0.05 μm to grind and polish the surface of the glassy carbon electrode in turn to obtain a mirror-like surface. The glassy carbon electrode is then rinsed with anhydrous ethanol and ultrapure water, respectively, and heated and dried under an infrared lamp to obtain a bare glassy carbon electrode.

[0098] Electrochemical detection:

[0099] The Cu-MOF@MnCO3 modified glassy carbon electrode, Cu-MOF modified glassy carbon electrode, MnCO3 modified glassy carbon electrode and bare glassy carbon electrode obtained in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were used as working electrodes, saturated calomel electrode as reference electrode and platinum electrode as counter electrode, respectively. 2+ HAc-NaAc solution (pH = 4.5), and Hg-free 2+ The HAc-NaAc solution (pH = 4.5) was used as a buffer solution to obtain a comparison diagram of the DPV current signals of mercury ions and copper ions. Figure 6 The glassy carbon electrodes in the four experiments were exposed to 10 μM Hg 2+ HAc-NaAc buffer (pH = 4.5), and Hg-free 2 + Comparison of DPV current signals in HAc-NaAc buffer (pH=4.5).

[0100] Figure 6 a is the bare glassy carbon electrode in comparative example 3 in the presence of 10 μM Hg 2+ HAc-NaAc buffer (pH = 4.5), and Hg-free 2+ The DPV current signal comparison diagram in HAc-NaAc buffer (pH = 4.5) is as follows: Figure 6 As shown in a, in the absence of Hg 2+ In the buffer containing Hg 2+ In the buffer solution, GCE detected the response current peak between -0.2 and 0.4 V, proving that the peak at 0.2 to 0.4 V was Hg 2+ The response current peak.

[0101] Figure 6 b is the MnCO3 modified glassy carbon electrode in comparative example 2 in the presence of 10 μM Hg 2+ HAc-NaAc buffer (pH = 4.5), and Hg-free 2+The DPV current signal comparison diagram in HAc-NaAc buffer (pH = 4.5) is as follows: Figure 6 As shown in b, in the absence of Hg 2+ In the buffer solution, no response current peak was detected by MnCO3 / GCE, which proves that MnCO3 2+ There is no interference in the detection of Hg 2+ In the buffer solution, Hg detected by MnCO3 / GCE 2+ The peak current of the response of MnCO3 to Hg 2+ The detection has the effect of signal amplification.

[0102] Figure 6 c is the Cu-MOF modified glassy carbon electrode in comparative example 1 in the presence of 10 μM Hg 2+ HAc-NaAc buffer (pH = 4.5), and Hg-free 2+ The DPV current signal comparison diagram in HAc-NaAc buffer (pH = 4.5) is as follows: Figure 6 c shows that in the absence of Hg 2+ In the buffer solution, Cu-MOF / GCE detected Cu near 0 V potential. 2+ The peak current response comes from the Cu 2+ The reduction of 2+ In the buffer, Cu 2+ The peak value was significantly increased, and compared with blank GCE, Hg 2+ The current response has a slight increase of 1.5 times, which is due to the 2+ During the detection process, Hg in the electrolyte 2+ The Cu in the Cu-MOF@MnCO3 matrix 2+ Reduced to Cu + , some Cu + Released into the electrolyte, the holes on the surface of the sensing electrode increase, promoting the Hg 2+ When Hg 2+ When the content increases, it will also reversely promote the Cu in the Cu-MOF@MnCO3 matrix. 2+ Reduced to Cu + This reaction.

[0103] Figure 6 d is the Cu-MOF@MnCO3 modified glassy carbon electrode in Example 1 in the presence of 10 μM Hg 2+ HAc-NaAc buffer (pH = 4.5), and Hg-free 2+The DPV current signal comparison diagram in HAc-NaAc buffer (pH = 4.5) is as follows: Figure 6 As shown in d, in the absence of Hg 2+ In the buffer solution, Cu detected by Cu-MOF@MnCO3 / GCE 2+ The peak current of Cu-MOF / GCE increased by 5 times compared with that of Cu-MOF / GCE, proving that MnCO3 promoted the 2+ The reduction of Cu 2+ The signal intensity of the reduction reaction. 2+ In the buffer solution, Hg detected by Cu-MOF@MnCO3 / GCE 2+ The peak current of Cu-MOF@MnCO3 / GCE was not affected compared with that of MnCO3 / GCE, which proved that Cu-MOF@MnCO3 / GCE can amplify Cu 2+ While retaining the peak current, the MnCO3 2+ Detection signal amplification effect.

[0104] In summary, the electrochemical sensor prepared by the present invention has good anti-interference and stability for the detection of mercury ions; under optimized test conditions, it exhibits high detection sensitivity, wide detection range, and low detection limit for mercury ions, and has good application prospects in the field of mercury ion detection.

[0105] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.

Claims

1. A method for preparing a glassy carbon electrode modified with Cu-MOF@MnCO3, characterized in that: The following steps are involved: S1. Preparation of Cu-MOF@MnCO3 powder S1.1: Add 2-aminoterephthalic acid and CuNO3·3H2O to DMF at room temperature, transfer to a polytetrafluoroethylene reactor after ultrasonic treatment, and stand at 90-100°C for 24-26 hours; then cool to room temperature, centrifuge, wash and dry the obtained precipitate to obtain Cu-MOF powder; Wherein, the molar ratio of 2-aminoterephthalic acid to CuNO3·3H2O is 2 to 4:5; S1.2: Add the Cu-MOF powder in step S1.1 and an equal amount of MnCO3 powder to DMF, perform ultrasonic treatment and centrifugal separation, wash the obtained precipitate, and vacuum dry it to obtain Cu-MOF@MnCO3 powder; S2. Electrode Pretreatment Take a glassy carbon electrode, grind and polish the surface of the glassy carbon electrode, then clean the surface of the glassy carbon electrode, heat and dry it under an infrared lamp for standby use; S3. Electrode Modification Cu-MOF@MnCO3 powder is added to DMF, and a suspension is obtained after ultrasonic treatment; the suspension is dropwise applied onto the surface of the glassy carbon electrode treated in step S2, and heated and dried under an infrared lamp to obtain a Cu-MOF@MnCO3 modified glassy carbon electrode.

2. The preparation method according to claim 1, characterized in that: In step S1.1, the duration of the ultrasonic treatment is 3 to 7 minutes; the working parameters of the centrifugal separation are: the rotation speed is 8000 to 9000 rpm, and the centrifugal time is 3 to 6 minutes; the selected detergent is anhydrous ethanol; the drying temperature is 50 to 70°C, and the drying time is 18 to 20 hours.

3. The preparation method according to claim 1, characterized in that: In step S1.2, the method for preparing the MnCO3 powder comprises the following steps: S1.2.1: Mix ethylene glycol and ultrapure water in a ratio of 1:1, add MnSO4 powder, and stir under ultrasonication until completely dissolved to obtain a mixed solution; S1.2.2: At room temperature, add NaHCO3 solution dropwise to the mixed solution in step S1.2.1 and continue stirring for 4 to 6 hours; then centrifuge and wash the obtained precipitate, and vacuum dry it to obtain MnCO3 powder.

4. The preparation method according to claim 1, characterized in that: In step S1.2.2, the molar ratio of MnSO4 to NaHCO3 is 1:1 to 1.

5.

5. The preparation method according to claim 1, characterized in that: In step S1.2, the duration of the ultrasonic treatment is 35 to 50 minutes; the working parameters of the centrifugal separation are: the rotation speed is 8000 to 9000 rpm, and the centrifugal time is 4 to 6 minutes; the selected detergent is anhydrous ethanol; the vacuum drying temperature is 50 to 70°C, and the drying time is 10 to 14 hours.

6. The preparation method according to claim 1, characterized in that: In step S2, the surface of the glassy carbon electrode is ground and polished using aluminum oxide powders with particle sizes of 0.3 μm and 0.05 μm respectively; and the ground and polished glassy carbon electrode is cleaned using anhydrous ethanol and ultrapure water respectively.

7. The preparation method according to claim 1, characterized in that: In step S3, the relationship between the drop coating amount of Cu-MOF@MnCO3 and the diameter of the glassy carbon electrode is 0.5×10 -3 ~1×10 -3 mg / 1mm.

8. The preparation method according to claim 1, characterized in that: In step S3, the ultrasonic treatment duration is 20 to 40 minutes.

9. A glassy carbon electrode modified with Cu-MOF@MnCO3 prepared by the preparation method according to any one of claims 1 to 8.

10. An electrochemical sensor comprising the glassy carbon electrode according to claim 9.

Citation Information

Patent Citations

  • Preparation method and application of PCT electrochemical immunosensor based on AuNPs / Cu-MOF marking

    CN106324060A

  • Method for detecting chloride ion concentration in lithium hexafluorophosphate by using Ag3PO4 / Cu-MOF modified glassy carbon electrode

    CN115728366A

  • Electrochemiluminescence sensor for detecting endocrine disrupter based on internal filtering effect as well as preparation and application of electrochemical luminescence sensor

    CN116660339A

  • AuNPs (at) Cu-MOF / MWCNTs surface modification electrochemical sensor and preparation method and application thereof

    CN117347445A

  • MIPWS2-ACCu-MOF (199) modified glassy carbon electrode, preparation method thereof and method for electrochemically sensing and detecting perfluorooctane

    CN118032890A